2008
DOI: 10.1167/iovs.07-1038
|View full text |Cite
|
Sign up to set email alerts
|

Antiadhesive Character of Mucin O-glycans at the Apical Surface of Corneal Epithelial Cells

Abstract: These results indicate that epithelial O-glycans contribute to the antiadhesive properties of cell surface-associated mucins in corneal epithelial cells and suggest that alterations in mucin O-glycosylation are involved in the pathology of drying mucosal diseases (e.g., dry eye).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 33 publications
0
45
0
1
Order By: Relevance
“…[23] MUC16 can help in the formation of a disadhesive barrier, [24] and in regulating the mucosal defenses of the epithelial cell layer. [25] CA125 is identified as a 5797 -base pair cDNA isolated from the OVCAR-3 cDNA library.…”
Section: Discussionmentioning
confidence: 99%
“…[23] MUC16 can help in the formation of a disadhesive barrier, [24] and in regulating the mucosal defenses of the epithelial cell layer. [25] CA125 is identified as a 5797 -base pair cDNA isolated from the OVCAR-3 cDNA library.…”
Section: Discussionmentioning
confidence: 99%
“…The mucins of undifferentiated epithelial cells are under-glycosylated. They lack the carbohydrate mucin antigen H185, which is expressed during differentiation Sumiyoshi et al, 2008).…”
Section: Transcellular Uptake Of Dye and Intercellular Spreadmentioning
confidence: 99%
“…Using human ocular mucins extracted and purified from human conjunctival tissue using classical mucin purification techniques, Berry et al demonstrated that the number of mucin-mucin interactions is minimal as compared to mucin-mica interactions. More recently, the role of cell surface O-glycans in providing boundary lubrication has been studied using static and dynamic flow adhesion assays in human corneal epithelial cells treated with benzyl-α-GalNAc, a chemical primer commonly used to suppress the elongation of O-glycan chains [21]. These experiments demonstrated that the cell surface character of corneal epithelial cells producing mucin O-glycans is more anti-adhesive than that of cells with altered O-glycans.…”
Section: Roles For Mucin O-glycans In the Glycocalyxmentioning
confidence: 99%